1984
DOI: 10.1017/s0022172400064871
|View full text |Cite
|
Sign up to set email alerts
|

A search for the source ofCampylobacter jejuniin milk

Abstract: SUMMARYSamples of milk from 1501 cows with mastitis were negative for Campylobacter jejuni. The faeces of 74 healthy Friesian cows were screened for C. jejuni: 13 % of the samples were positive during the summer when the cows were on pasture, and 51 % were positive in the winter when the cows were housed. Positive samples contained on average 1 x 104 campylobacters per g faeces.It is concluded that faecal contamination rather than udder infection is the means by which campylobacters enter milk and thereby infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 8 publications
1
22
0
2
Order By: Relevance
“…Up to 6% of bulked raw milk samples in the United Kingdom yield campylobacters (43). Cross-contamination of milk occurs from feces during milking or from Campylobacter mastitis (44,45), and failed pasteurization also has been associated with out-breaks of infection (41,46,47). Studies have shown very high rates of Campylobacter contamination among supermarket chickens (48).…”
Section: Reservoirs and Transmission Of Infectionmentioning
confidence: 99%
“…Up to 6% of bulked raw milk samples in the United Kingdom yield campylobacters (43). Cross-contamination of milk occurs from feces during milking or from Campylobacter mastitis (44,45), and failed pasteurization also has been associated with out-breaks of infection (41,46,47). Studies have shown very high rates of Campylobacter contamination among supermarket chickens (48).…”
Section: Reservoirs and Transmission Of Infectionmentioning
confidence: 99%
“…fetus (Devlin & McIntyre, 1983;Harvey & Greenwood, 1983;Klein et al 1986), C. cinaedi and C. fennelliae (Totten et al 1985) may also be involved in enteritis. C. jejuni has been isolated from a wide range of animal species (Luechtefeld, Cambre & Wang, 1981;Rosef et al 1983;Fricker & Metcalfe, 1984;Waterman, Park & Bramley, 1984) and water (Knill, Suckling & Pearson, 1982;Bolton, Coates & Hutchinson, 1985). Unpasteurized cows' milk (Hutchinson et al 280 S. M. ARIMI, C. R. FRICKER AND R. W. A.…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of milk can be caused by direct excretion from an asymptomatic cow with mastitis (17) or, more commonly, by fecal contamination during milking (43). The majority of outbreaks have occurred after the consumption of raw milk (44), although improperly pasteurized milk (1) and postpasteurization contamination have been implicated as sources of outbreaks.…”
mentioning
confidence: 99%